HUBUNGAN MOTIVASI DAN KOMITMEN KERJA PERAWAT DENGAN PENERAPAN KESELAMATAN PASIEN DI RUANG INTENSIF RSUP SANGLAH DENPASAR - Krisnawati, Komang Menik Sri; Wijaya, I Putu Ganda; Suarjana, Ketut (Coping: Community of Publishing in Nursing, 2016)
Background and purpose : The application of patient safety in hospitals is influenced role of HR service providers. HR has the largest population of nearly 40% compared to other workers and have a period of direct contact with patients is a nurse. This study aims to determine the relationship between nurse motivation and commitment to work with the application of patient safety. Methods: This research is observational study with cross sectional approach. The sample consisted of 112 nurse selected by total sampling. Results: Based on the Chi-Square Tests, correlation nurse motivation and nurse commitment to work with implementation of patient safety obtained p value of 0.000 means there is a relationship between nurse motivation and nurse commitment to work with implementation of patient safety. Conclusion :Motivation and commitment to work and nurse characteristics (age, education, marital status, employment status, length of employment) is jointly associated with the implementation of patient safety. Factors working commitment of the most dominant influence on the application of patient safety compared with the motivational factors of nurses and nurse characteristics, so the need for efforts to increase the commitment of nurses through socialization associated with understanding the vision and mission of the hospital as well as the achievement of the performance indicators of good nurses by increasing the quality of nursing through education formal or informal ongoing basis, increased motivation of nurses, especially in terms of adjustment of incentives, leadership and commitment to create a situation conducive work.  Keywords: Commitment, Implementation of Patient Safety, Motivation